2011
DOI: 10.1111/j.1740-0929.2011.00893.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between adipose maturity and fatty acid composition in various adipose tissues of Japanese Black, Holstein and Crossbred (F1) steers

Abstract: The amount of monounsaturated fatty acid (MUFA) is intimately related to adipose softness, melting point (MP) and flavor in beef. Stearoyl-CoA desaturase (SCD) is a main gene involved in MUFA synthesis. Mature adipose tends to be highly saturated, whereas immature or maturing adipose is highly unsaturated when chronologically based, so the degree of non-saturation can be an index of adipose maturity. In this study, three different adipose tissues (coelomic (CL), perirenal (PR), and subcutaneous (SC)) from thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 34 publications
6
12
0
Order By: Relevance
“…These findings agree with differences in Δ-9 desaturase indices (Jiang et al, 2013) and mRNA abundance (Lee et al, 2011) reported previously. The proportions of 22:5n-3 and 20:4n-6 were the only n-3 and n-6 PUFA influenced by fat depot, with SCF having larger (P <0.05) proportions of these FA compared with PRF (Table 3).…”
Section: Fatty Acids Of Dietary or Endogenous Originsupporting
confidence: 83%
See 2 more Smart Citations
“…These findings agree with differences in Δ-9 desaturase indices (Jiang et al, 2013) and mRNA abundance (Lee et al, 2011) reported previously. The proportions of 22:5n-3 and 20:4n-6 were the only n-3 and n-6 PUFA influenced by fat depot, with SCF having larger (P <0.05) proportions of these FA compared with PRF (Table 3).…”
Section: Fatty Acids Of Dietary or Endogenous Originsupporting
confidence: 83%
“…These dissimilarities could be linked to the proportions of 18:0, which exhibit a similar pattern. Generally, less mature fat depots situated externally, such as SCF, are less saturated than mature fat depots situated internally, such as PRF (Christie, 1978;Lee et al, 2011;Jiang et al, 2013). This is linked to a greater Δ-9 desaturase activity index in external depots as opposed internal ones, and replacement of 18:0 with c9-18:1 in external fat depots.…”
Section: Fatty Acids Of Dietary or Endogenous Originmentioning
confidence: 99%
See 1 more Smart Citation
“…The beef performance index (BPI) is 5.66 to 6.76 kg/cm for adult bulls and 4.06 to 4.59 kg/cm for adult cows over Yanbian yellow cattle. Fat percentages in carcass are different between different cattle breeds and fat depots in the bovine body are developed according different order (Lee et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there was no correlation between the MUFA content and the EP (R 2 = 0.040). A high MUFA concentration and lower MP in adipose tissue contributes to a desirable beef flavor (Yang et al 1999;Lee et al 2011), while a higher PUFA and MUFA in adipose tissue contribute to a lower fat MP (Smith et al 1998;Pitchford et al 2002;De Smet et al 2004;Daley et al 2010;Uemoto et al 2010). These reports strongly support the MP measured using the slip point method that would be reflected in the MUFA content in IAT.…”
Section: Resultsmentioning
confidence: 58%